Tweeting is leading : how senators communicate and represent in the age of Twitter - Russell, Annelise (New York : OXford University Press, 2021)
"Social media is changing the business of representation and lawmaker reputation-building, and this book uses the U.S. Senate to illustrate the constituent-driven nature of political communication. I offer a critical analysis of senators' communication on Twitter, the forces that shape it, and the agendas that result. Senators strategically communicate a political image that reflects their unique political persona. They have to decide what they want to be known for, crafting communications that prioritize legislation, constituent service, and party politics in ways that meet the interests of their constituencies and foster promising electoral returns. Senators' communicated, public priorities - what I term the rhetorical agenda - offers a necessary tool for understanding how senators link their carefully crafted public image with potential voters. The rhetorical agenda uses more than 180,000 lawmaker tweets to challenge what we know about representation, removing the institutional and political constraints on congressional communication and giving lawmakers a messaging platform where individual discretion is high, the relative costs are low, and someone is always watching"--
: Introduction -- Rhetorical agendas : a new framework for Senate representation -- Communicating Congressional priorities in the digital age -- "Short, not-so-sweet, and to (some) point" : Senate Tweets in 2013 and 2015 -- Categorizing Senators' Tweets and styles of communication -- Putting policy first : building a reputation as a policy wonk -- All politics is local : senators prioritize constituent service -- Partisan agendas : two parties, two patterns of partisan rhetoric -- Prioritization and representation : a future for social media and agenda-setting.
Includes bibliographical references and index.
Keywords: United States. -- Congress. -- Senate -- Constituent communication; Twitter; United States. -- Congress. -- Constituent communication; Microblogs -- Political aspects -- United States